From Child Welfare to Child Well-Being An International Perspective on Knowledge in the Service of Policy Making - Kamerman, Sheila B.; Phipps, Shelley; Ben-Arieh, Asher; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This unique and impressive collection is an outstanding tribute to Al Kahn, one of the most influential researchers on child welfare in the 20th century. The book provides an exceptional opportunity to "experience" the history of the past 50 years of child welfare as well as its current status and future. It takes the reader through the movement, from a deficit-oriented policy to a developmental model, from a targeted and selective strategy to a universal approach, and from child welfare to child well-being. Written by renowned experts, the chapters are organized into five clusters. The first one includes Al Kahn$1 (Bs last written contribution to the field and looks at how children and families have changed over time as has the research on their well-being. The next two clusters focus on the traditional child welfare system and on different theoretical perspectives. The fourth and fifth clusters focus on economic support for child and family well-being and a discussion of current child well- being issues.s
Opening Chapters -- From (3z(BChild Saving(3y (Bto (3z(BChild Development(3y(B? -- From Child Welfare to Children Well-Being: The Child Indicators Perspective -- Child Welfare -- An Historical Perspective on Child Welfare -- Testing Practice Wisdom in Child Welfare -- Understanding Child Maltreatment Systems: A Foundation for Child Welfare Policy -- Fact-Based Child Advocacy: The Convergence of Analysis, Practice, and Politics in New York City -- Using Early Childhood Wellbeing Indicators to Influence Local Policy and Services -- Social Policy and the Transition to Adulthood for Foster Youth in the US -- Theoretical Perspectives -- The Ecological Perspective on the Human Rights of Children -- Social Problem Construction and Its Impact on Program and Policy Responses -- The Development of International Comparative Child and Family Policies -- Using Child Indicators to Influence Policy: A Comparative Case Study -- In Children$1 (Bs Voices -- Economic Support -- Assuring Child Support: A Re-assessment in Honor of Alfred Kahn -- Child Poverty and Antipoverty Policies in the United States: Lessons from Research and Cross-National Policies -- Income Support for Families and the Living Standards of Children -- An International Perspective on Child Benefit Packages -- Canadian Policies for Families with Very Young Children in International Perspective -- Child Poverty in Upper-Income Countries: Lessons from the Luxembourg Income Study -- Issues in ChildWell-Being -- Early Childhood Education and Care -- Childcare Policies in France: The Influence of Organizational Changes in the Workplace -- Regional Case Studies$1 (BChild Well Being in Europe -- Conclusion -- Child, Family, and State: The Relationship Between Family Policy and Social Protection Policy.s
Keywords: Quality of Life; Social policy; Social work; Quality of Life -- Research; Developmental psychology; Social Sciences, general; Quality of Life Research; Social Policy; Social Work; Child and School Psychology